Endoscopic transnasal approach and intraoperative navigation for the treatment of isolated blowout fractures of the medial orbital wall. Issue 10 (December 2015) - Copelli, C.; Manfuso, A.; d'Ecclesia, A.; Catanzaro, S.; Cassano, L.; Pederneschi, N.; Tewfik Hanna, K.; Cocchi, R.
Abstract: The aim of this study is to describe the reduction of medial orbital wall fractures using a combination of two different techniques: the endoscopic reduction and the navigation aided reconstruction. The endoscopic approach avoids an external incision and allows the observation of the fracture site clearly. Navigation-aided reconstruction is essential to achieve precise and predictable results in orbital reconstruction. It consists in an ideal virtual reconstruction of the target area created using a mirroring tool, and superimposing and comparing the unaffected and the affected sides. This technique opens a broad spectrum of possible surgical approaches, especially in situations in which anatomical landmarks for precise positioning of bone fragments, or bone grafts, are missing. This study is the first to combine these two techniques. The study was carried out in seven patients who underwent endoscopic reduction of isolated blowout fractures of the medial orbital wall and navigation-aided reconstruction at the authors' institution. This pilot study clearly shows that a combination of the endoscopic reduction and the navigation-aided reconstruction provides functional results and great advantages in terms of anatomical preservation and postoperative morbidity.